Creation of a "Patient" Hospital Escape Room Experience to Reduce Harm and Improve Quality of Care. Issue 1 (January 2021) - San Martin, Layla; Walsh, Heather; Santerre, Mary; Fortkiewicz, Justine; Nicholson, Laura
Abstract : Background: Increases in nursing documentation requirements, adherence to regulatory standards, and workforce diversity add to the complexity of delivering safe patient care. Purpose: The aim was to reinforce elements of quality and safety in patient care delivery. Approach: In an effort to deliver necessary, though often dull, regulatory information to nursing staff, a team of nurse educators and nursing quality leaders used the concepts of a popular social game to develop an escape room. Outcomes: The escape room was conducted with nearly 100 learners with both a regulatory focus and a patient safety focus with success. Participants stated that teamwork, communication, and problem-solving were necessary to escape the room; nearly 60% indicated the escape room experience would contribute to changes in their nursing practice. Conclusions: The escape room template can be easily modified to target a myriad of learning objectives and learners of varying levels of experience. Abstract : Supplemental Digital Content is Available in the Text.